Case report: Cortico-ocular interaction networks in NBA2K - Stamatis, Andreas; Garcia-Retortillo, Sergi; Morgan, Grant B.; Sanchez-Moreno, Ana (Frontiers in Network Physiology, 2023)
The sport industry has never seen growth such as eSports’. Using synchronized monitoring of two biological processes on a 25-year-old gamer, we investigated how his brain (via EGG) and eyes (via pupil dilation) interacted dynamically over time as an integrated network during NBA2K playing time. After the spectral decomposition of the different Brain and Eye signals into seven frequency bands, we calculated the bivariate equal-time Pearson’s cross-correlation between each pair of EEG/Eye spectral power time series. On average, our results show a reorganization of the cortico-muscular network across three sessions (e.g., new interactions, hemispheric asymmetry). These preliminary findings highlight the potential need for individualized, specific, adaptive, and periodized interventions and encourage the continuation of this line of research for the creation of general theories of networks in eSports gaming. Future studies should recruit larger samples, investigate different games, and explore cross-frequency coordination among other key organ systems.